A viscoelastic‐viscoplastic model with non associative plasticity for the modelling of bonded joints at high strain rates. (October 2016) - Dufour, Ludovic; Bourel, Benjamin; Lauro, Franck; Haugou, Gregory; Leconte, Nicolas
Abstract: The purpose of this work is to present a constitutive model able to represent the behaviour of rubber-toughened adhesive joints under dynamic loading. A fully coupled viscoelastic–viscoplastic damage model at finite strains developed for mineral filled semi-crystalline polymer is identified for an epoxy adhesive. The parameters of the model are identified from experimental tests undertaken on bulk material in compression and tension at several loading speeds. In order to validate the accuracy of the model to represent bonded joints, a specific dynamic Arcan device is used. Experimental tests on this apparatus are carried out for tensile, shear and mixed tensile/shear loadings at 1 mm/s, 10 mm/s and 100 mm/s. A very good agreement between experimental and numerical results is obtained for a large strain rate range and for various stress states.